Effect of HF and ER additions on the mechanical properties and microstructure of AL-MG-SC-ZR system alloys - E. V. Aryshenskii; V. Yu. Aryshenskii; A. A. Ragazin; D. Yu. Rasposienko; F. V. Grechnikov; V. V. Makarov; S. V. Konovalov (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение, 2024)
The study addresses the effect of 1580 and 1590 alloys cold rolled strip annealing practices on the alloys’ grain structure and mechanical properties. The 1590 alloy differs from the 1580 alloy by hafnium and erbium additions. Samples of such alloys were produced by casting into a steel mold. After that they were homogenized during 4 h at 440°С. Then the samples were hot rolled at 440°С, with further cold rolling to 2 mm, with the cumulative percentage reduction equal to 66%. The cold rolled strip was annealed at the temperature ranging from 330 to 440°С with 1 h soaking. The sizes and morphology of Al3Sc strengthening nanoparticles were examined in homogenized condition using transmission microscopy. The mechanical properties and grain structure were defined in cold rolled and annealed conditions. During homogenizing annealing in the 1590 alloy finer strengthening nanoparticles are formed compared to the 1580 alloy. Such features of the microstructure can be explained by the presence of erbium, promoting formation of additional Al3Sc-type nanoparticles nuclei, and hafnium, preventing their further growth. Non-recrystallized structure was identified in both alloys after cold rolling and final annealing. The 1590 alloy has better mechanical properties, regardless of the annealing temperature, which is explained by a larger portion and smaller size of strengthening nanoparticles.